TRANSITIONS OUT OF CRIME new approaches on desistance in late adolescence. - Droppelmann, Catalina ([S.l.] : ROUTLEDGE, 2021)
This book contributes to our knowledge of desistance in a developing country. Offering an intercultural dialogue with mainstream explanations, Transitions Out of Crime analyses the transition from crime to conformity among a group of Chilean juvenile offenders. Desistance from crime is not just the cessation of criminal activity itself, but a process of acquiring roles, identities, and virtues; of developing new social ties, and of inhabiting new spaces. This book offers new evidence that shows that the traditional binary between the reformed desister' and the anti-social persister' is inaccurate and that the road to desistance contains various oscillations between crime and conformity. Furthermore, this study shows the role that gender plays in shaping, limiting and structuring pathways away from crime. Written in a clear and direct style, this book will appeal to those engaged in criminology, sociology, penology, desistance, rehabilitation, gender studies and all those interested in the transition from crime to conformity outside the Anglo-American orthodoxy.
OCLC-licensed vendor bibliographic record.
Keywords: Juvenile delinquents -- Rehabilitation -- Developing countries; Crime -- Developing countries; Conformity -- Developing countries; Criminals -- Rehabilitation -- Developing countries; SOCIAL SCIENCE / Criminology